2020
DOI: 10.1177/2277977920957954
|View full text |Cite
|
Sign up to set email alerts
|

Yulu: Moving Towards a Sustainable Future

Abstract: The rapidly rising rate of urbanization, which is closely linked to economic growth, has exposed the world to several challenges such as inequality, environmental degradation, traffic congestion, infrastructural concerns and social conflicts. Therefore, urban sustainability has emerged as one of the most debatable discussions across the world. The existing network of transportation can no longer keep up with the growing demand in metropolitan cities. Short distance travel has become an unresolved issue for dai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 8 publications
1
0
0
Order By: Relevance
“…First, results indicated that environmental consciousness, economic benefits, social aspects, and perceived risks have a significant impact on Generation Z's intention to use shared mobility platforms in India. This is consistent with the results of the existing literature [12,13,15,41,49,62,78,79].…”
Section: Discussionsupporting
confidence: 93%
“…First, results indicated that environmental consciousness, economic benefits, social aspects, and perceived risks have a significant impact on Generation Z's intention to use shared mobility platforms in India. This is consistent with the results of the existing literature [12,13,15,41,49,62,78,79].…”
Section: Discussionsupporting
confidence: 93%